Chromium modulates expressions of neuronal plasticity markers and glial fibrillary acidic proteins in hypoglycemia-induced brain injury - Şahin, Kazım; Tuzcu, Mehmet; Orhan, Cemal; Ali, Shakir; Şahin, Nurhan; Gencoglu, Hasan; Komorowski, James R. (Pergamon-Elsevier Science Ltd, 2013)
Aims: This experiment investigated if chromium (Cr) as Cr-histidinate (CrHis) and Cr29 picolinate (CrPic) have a protective role in rats with hypoglycemia-induced brain injury, assessed by neuronal plasticity and regeneration potential. Main methods: Male Sprague-Dawley rats were prospectively divided into 2 groups: control and hypoglycemic (induced by insulin administration, 15 U/kg, i.p., n = 56). Hypoglycemic rats were then received randomly 1) none, 2) dextrose (on the day of sampling), 3) CrHis, or 4) CrPic. Cr-chelates were delivered via drinking water (providing 8 Kg elemental Cr per day) for one week prior to the hypoglycemia induction. The expressions of neuroplasticity markers [neural cell adhesion molecule (NCAM), growth-associated protein-43 (GAP-43), glial fibrillary acidic protein (GFAP)], glucose transporters (GLUT), and nuclear transcription proteins [nuclear factor-kappa (NF-kappa B), nuclear factor (erythroid-derived 2)-like 2 (Nrf2), and 4-hydroxyl nonenal (HNE)] were determined using Western blot. Key findings: Hypoglycemia caused increases in the expressions of GLUT-1, GLUT-3, GFAP, NF-kappa B and HNE and decreases in the expression of NCAM's, GAP-43 and Nrf2 in the hippocampus, cerebellum, and cortex. Cr-chelates suppressed expressions of GLUTs, GFAP, NF-kappa B and HNE expressions and enhanced expressions of NCAM, GAP-43 and Nrf2, which were more notable for CrHis than for CrPic. Significance: In conclusion, hypoglycemia leads to cerebral injury and Cr-chelates, particularly CrHis have protective and regeneration potential in cerebral tissues through modulating neuroplasticity markers and nuclear transcription proteins as well as facilitating glucose transporters. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Hypoglycemia; Chromium; Neuronal plasticity; Glucose transporter; Transcription factors